An analysis of paragraph (c) of the 'gross income' definition and the term 'services rendered' - Kramer, Tanya H. (Department of Commercial Law, 2023)
The South African tax system operates as a dual system of direct and indirect taxation. Direct taxation is imposed directly on taxpayers be they natural or legal by nature, by imposing tax on the income of those taxpayers. This is known as income tax. Another form of direct taxation is estate duty. By contrast, indirect taxation is where a transaction or consumption, rather than an entity is taxed. An example of this is VAT. The South African Revenue Service currently imposes income tax on individuals, companies and other taxable entities. The legislation in terms of which income tax is imposed is the Income Tax Act 58 of 1962. The income Tax Act is an ever-changing piece of legislation, as each year it is amended to accommodate the changing economic environment as well as the tax proposals put forward by the Minister of Finance. §5 of the Income Tax Act governs the annual payment of tax according to the rates established at the beginning of each year of assessment. This is known as normal tax. The section indicates that tax can be levied against any person or company. The term 'person' is defined in § I of the Act so as to include a deceased estate, an insolvent estate and a trust, and a company, in the same section, is defined to include a close corporation.